2020
DOI: 10.1002/cam4.3481
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genomic analysis identifies a genetic mutation model predicting response to immune checkpoint inhibitors in melanoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 55 publications
(149 reference statements)
0
22
0
Order By: Relevance
“…Nevertheless, all of these mutations are weighted the same in TMB scoring systems, highlighting the limitations of TMB as a predictive biomarker for ICI. Recently, it has been reported that TMB-based survival prediction can be improved by optimizing the TMB algorithm 20 or by establishing gene mutation-based signatures 21 , 22 . We therefore investigated the genomic determinants of ICIs benefits in gastrointestinal cancer and developed a gene mutation-based risk model containing the most decisive prognosis-related genes to better predict the clinical outcomes of immunotherapy in patients with gastrointestinal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, all of these mutations are weighted the same in TMB scoring systems, highlighting the limitations of TMB as a predictive biomarker for ICI. Recently, it has been reported that TMB-based survival prediction can be improved by optimizing the TMB algorithm 20 or by establishing gene mutation-based signatures 21 , 22 . We therefore investigated the genomic determinants of ICIs benefits in gastrointestinal cancer and developed a gene mutation-based risk model containing the most decisive prognosis-related genes to better predict the clinical outcomes of immunotherapy in patients with gastrointestinal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical outcome of immunotherapy is not easy to predict and, in some cases, is not positive for patients. Indeed, unlike targeted therapy, which has predictive response markers, such as the BRAF mutation, validated biomarkers for the immunotherapeutic agents still need to be approved [45,46]. In recent years, gene sequencing studies have shown that the TMB, neoantigen load (NL) or PDL1 expression degree are often associated with an increased response to immunotherapy [47,48].…”
Section: Genomics Approachesmentioning
confidence: 99%
“…In recent years, gene sequencing studies have shown that the TMB, neoantigen load (NL) or PDL1 expression degree are often associated with an increased response to immunotherapy [47,48]. However, undefined cut-off and weak reliability of prediction have not given significant results [46,49]. Thus, in melanoma, the research of new predictive biomarkers appears fundamental to discriminate the patients and to avoid unnecessary and sometimes dangerous treatments.…”
Section: Genomics Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…RTK/RAS pathway gene alterations showed a tendency for higher TMB, with every TMB-high patient being in the RTK/RAS pathway alteration group also (Extended Data Fig 6e-f). Indeed, the RTK/RAS pathway is related to enhanced response to immunotherapy through stabilization or overexpression of PD-L1 [29][30][31] .…”
mentioning
confidence: 99%